Haploid Helps Phaeocystis Globosa Distribute to Deeper Dim Water, as Evidenced by Growth and Photosynthetic Physiology - Zhuang, Junlian; Lu, Jiachang; Cao, Kun-Fang; Li, Jie (Frontiers in Marine Science, 2022)
Phaeocystis globosa has a haplo-diplontic alternative life cycle and is an important causative species of harmful algal blooms. Diploid solitary cells of Phaeocystis can form colonies and bloom in the surface water. However, haploid cells are abundant in deep water rather than surface water. We hypothesize that the haploid cells of Phaeocystis globosa could better adapt to deep dim water than its diploid cells. Haploid and diploid solitary cells of P. globosa were cultured with eutrophic medium (f/2) under moderately low (15 µmol photons m-2 s-1), extremely low (5 µmol photons m-2 s-1) and normal (60 µmol photons m-2 s-1) irradiance conditions. The results showed that irradiances used in this study did not induce reactive oxygen species (ROS) damage in either haploid or diploid cells. Both haploid and diploid solitary cells grew faster at higher irradiance during the initial exponential growth phase. However, the haploid abundances under moderately and extremely low irradiances were higher than that under normal irradiance after the exponential growth phase, but diploid cells formed more colonies at higher irradiances. An increase in the photosynthetic pigments (PSC) ratio combined with a reduction in photoprotective pigments (PPC) ratio were found in both ploidies with decreasing irradiance, but the ratios of PSC and PPC and xanthophyll cycle pigments were significantly higher in haploid cells than in diploid cells. For haploids, the highest potential photochemistry efficiency of photosystems П was found under extremely low irradiance, but for diploids, it was observed under moderately low irradiance. The results suggest that both haploid and diploid solitary cells of P. globosa in eutrophic water can survive under low-light conditions, but haploid cells have an advantage in extremely low irradiance.